1989
DOI: 10.1007/bf01965266
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily versus thrice-daily administration of netilmicin in combination therapy ofPseudomonas aeruginosa infection in a man-adapted neutropenic animal model

Abstract: A granulocytopenic mouse model was used to elucidate the impact of dose spacing on the activity of netilmicin against Pseudomonas aeruginosa. A thigh infection was produced and then treated with netilmicin combined with azlocillin. Netilmicin was injected subcutaneously at decreasing doses every 20 min to result in plasma-concentration-time curves similar to those observed in patients on intravenous netilmicin treatment. A once-daily regimen was simulated and compared to a simulated conventional schedule of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, studies in neutropenic animals have shown a once daily regimen to be of equivalent or superior efficacy,46 47 48 and our meta-analysis showed no loss of efficacy with a single daily dose in neutropenic patients. Our analysis actually suggested that a single dose was superior to multiple doses when the percentage of pseudomonas isolates in a study was higher.…”
Section: Discussionmentioning
confidence: 53%
“…However, studies in neutropenic animals have shown a once daily regimen to be of equivalent or superior efficacy,46 47 48 and our meta-analysis showed no loss of efficacy with a single daily dose in neutropenic patients. Our analysis actually suggested that a single dose was superior to multiple doses when the percentage of pseudomonas isolates in a study was higher.…”
Section: Discussionmentioning
confidence: 53%
“…However, data from in-vitro and experimental in-vivo studies suggest that once-daily dosing of aminoglycoside might be at least as efficacious and potentially less toxic (Frame et al, 1977;Blaser, Stone & Zinner, 1985a;Gerber et al, 1989;Mattie, Craig & Pechere, 1989). Single-daily dosing of aminoglycosides has also been studied clinically (Powell et al, 1983;Hollender et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Our animal model is similar to models described by others (4,5). Unlike the previous investigators, we inoculated the microorganisms intraperitoneally to produce disseminated infection.…”
Section: Discussionmentioning
confidence: 98%